Group Theoretical Study of Certain Generating Functions for Modified Jacobi Polynomials - Elkhazendar, Marawan Baker (Journal of Informatics and Mathematical Sciences, 2012)
The object of the preset paper is to derive some generating functions with five parameters Lie-group for the modified Jacobi polynomial P_n^(α -n,β ) (x) by interpreting n, α -n, β simultaneously by using the Weisner’s group-theoretic method.